1977
DOI: 10.1002/1097-0142(197704)39:4<1686::aid-cncr2820390443>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the buccal mucosa associated with chronic oral polyvinyl chloride exposure.Report of a case

Abstract: The following case report describes a 22-year-old healthy man, non-smoker, non-drinker, who developed a squamous cell carcinoma of the buccal mucosa. The appearance of this unusual tumor in an unexpected clinical setting was unexplained until it was discovered that the patient had a lifetime habit of chewing plastic materials containing polyvinyl chloride (PVC). The extent and chronicity of his intense oral exposure to PVC is believed to be related to his subsequent development of an oral neoplasm. Attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In addition, other proposed causes for SCC in young people with no risk factors have included immunosuppression, 29-31 viral infection, 32 heritability, 33,34 trichinosis infection, 35 history of xeroderma pigmentosum or ichthyosiform dermatosis, [36][37][38][39][40] or oral exposure to polyvinyl chloride. 41 When all of these possible causes for SCC are accounted for, there is still a large number of patients with no known risk factors who have SCC develop. This study found that most (81%) of these young patients with no known risk factors overexpressed the p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other proposed causes for SCC in young people with no risk factors have included immunosuppression, 29-31 viral infection, 32 heritability, 33,34 trichinosis infection, 35 history of xeroderma pigmentosum or ichthyosiform dermatosis, [36][37][38][39][40] or oral exposure to polyvinyl chloride. 41 When all of these possible causes for SCC are accounted for, there is still a large number of patients with no known risk factors who have SCC develop. This study found that most (81%) of these young patients with no known risk factors overexpressed the p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment planning has been inconsistent, varying from relatively conservative efforts in some centers to more radical approaches than ordinarily seen in older adults with similar disease. Individual case reports [2,3,5,6,7] involving young patients with oral cancer all confirm the rarity of the disease and the poorer prognosis compared to older individuals. Venables and Craft [8] report 13 cases of carcinoma of the tongue in patients less than 30 years of age .…”
Section: Introductionmentioning
confidence: 97%
“…Aunque todavía no se puede clasificar a la marihuana y el hachís como substancias "dañinas", sí se debería insistir a la opinión pública sobre las propiedades carcinogénicas de las substancias inhaladas, que además del humo del tabaco, debería incluir la marihuana y el hachís, muy especialmente entre los jóvenes donde su consumo es mayor. Otros factores que han sido involucrados con menos frecuencia en población joven incluyen infección por papilomavirus 12 , hábitos dietéticos 13 , pobre higiene oral 14 , exposición crónica al cloruro de polivinilo 15 , e historia de xeroderma pigmentoso 16 . Sin embargo, muchas de las personas diagnosticadas de cáncer de lengua por debajo de 40 años no pertenecen a ninguno de estos grupos de riesgo, lo que ha llevado a implicar a factores genéticos.…”
Section: Introductionunclassified